Police Human Resource Policy in the Lodz region as a determinant of knowledge and organization's effective operation - Joanna Luczak (Institute of Economic Research (IER), 2017)
Human capital is the driving force of an organization that has a significant impact on its development and effective operation. The success of the organization depends to a great extent on its social potential. Successful recruitment ensures that the best employees ensure high quality work, which respectively translates into organizational development and competitiveness (Oleksyn 2010, pp. 34-36). The development of the organization is based on knowledge acquisition, skills and raising qualifications by its members. The aim of the paper is to analyze the conditionings related to the management of the police organizational units, which influence the appropriate recruitment of police officers for particular positions. The publication also attempts to investigate the importance of appropriate recruitment for the effectiveness of actions taken by police officers. The article presents issues exemplifying the analysis of human resource management in the field of human resource policy playing an important role in Police. The empirical part of the article was based on an analysis of the subject literature and police internal materials, but also on the basis of participant observation and expert interview. The paper presents an analysis of the recruitment process of police officers for vacant posts in Police units of the Lodz Region, introduced by the Human Resource Policy Concept. Although the Police was established to protect citizens' security and public order, its development and effective functioning are needed to further serve society. In order to do this, it is indispensable to recruit and employ proper and competent workers. Therefore, the recruitment and selection process is so significant.
Keywords: D73; D78; 330; public management; human resource management; police; recruitment; selection